2017
DOI: 10.1097/yic.0000000000000148
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events in children and adolescents treated with quetiapine

Abstract: Quetiapine is a low-affinity dopamine D2 receptor antagonist, approved for the treatment of bipolar disorder and schizophrenia in children and adolescents by the Food and Drug Administration, but not by European Medicine Agency. Although knowledge of adverse drug reactions in children and adolescents is scarce, quetiapine is increasingly being used for youth in Denmark. The aim of this case study is to discuss adverse drug events (ADEs) spontaneously reported to the Danish Medicines Agency on quetiapine used i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…However, extremely limited guidelines for its use are available in this population. A recent nationwide report demonstrated that off-label use of quetiapine in children and adolescents is prevalent in Denmark, and life-threatening adverse events involved seizure, QT-interval prolongation, and cerebral hemorrhage 3. Besides, this study implied that quetiapine could induce hyperprolactinemia, especially in minors 3.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…However, extremely limited guidelines for its use are available in this population. A recent nationwide report demonstrated that off-label use of quetiapine in children and adolescents is prevalent in Denmark, and life-threatening adverse events involved seizure, QT-interval prolongation, and cerebral hemorrhage 3. Besides, this study implied that quetiapine could induce hyperprolactinemia, especially in minors 3.…”
Section: Introductionmentioning
confidence: 63%
“…A recent nationwide report demonstrated that off-label use of quetiapine in children and adolescents is prevalent in Denmark, and life-threatening adverse events involved seizure, QT-interval prolongation, and cerebral hemorrhage 3. Besides, this study implied that quetiapine could induce hyperprolactinemia, especially in minors 3. Moreover, in some susceptible individuals, exposure to quetiapine overdoses can result in severe complications, such as coma, seizure, respiratory depression, arrhythmia, and even death 4.…”
Section: Introductionmentioning
confidence: 73%
“…192 Since some of those adverse events are life threatening, the off-label use of quetiapine in children and adolescents gives rise to safety concerns. 236 antagonist at dopamine D2 and D3 receptors. The body of evidence on the effectiveness of tiapride in the treatment of tics is still small.…”
Section: Systematic Review Of Dopamine Receptormentioning
confidence: 99%
“…Both researches by Wenzel‐Seifert et al 9 and Hasnain et al 10 observed that torsade de pointes (TdP) was in association with the use of newer antipsychotic drugs, which mainly included quetiapine. The widely reported cardiovascular side effects have also raised concerns of the Danish Medicine Agency or the European Medicine Agency, which has therefore been cautious about expanding the use of quetiapine 11,12 . In particular, the FDA have warned in the instructions that elderly patients with dementia‐related psychosis was associated with an increased risk of death from cardiovascular diseases (e.g., heart failure, sudden death) and infections (e.g., pneumonia) when treated with quetiapine.…”
Section: Introductionmentioning
confidence: 99%